Habituação do reflexo cócleo-palpebral em recém-nascidos a termo - Gonçalves, Maiara Santos (2007)
The present study aims to verify the occurrence of habituation of the blink reflex in full-term newborns; to examine whether there is an association between the occurrence of habituation and gender; to determine which would be the most promising neurobehavioral state to achieve this phenomenon and to establish the number of sound stimuli needed to provoke habituation. The population consisted of 100 newborns in the Early Detection of Infant Hearing Loss program of the Speech Therapy and Audiology Course at the Federal University of Santa Maria. The babies were born at the University Hospital of Santa Maria and were observed during one minute to establish their neurobehavioral state. For the habituation research, agogo bells were played in a sequence of up to 30 sound stimuli every two seconds at intensity close to 90 dB SPL. We considered habituation when the child stopped presenting the blink reflex for three consecutive times, and the absence of habituation was when the child presented the blink reflex along the trial. Data analysis was made with association and adherence Chi-square tests. From the investigated population of 100 neonates, 64% (n=64) presented habituation of the blink reflex and 36% (n=36) didn t. Regarding the 64 children that presented the blink reflex, 42,2% (n=27) were male and 57,8% (n=37), female. Interruption of response on the first 10 stimuli occurred in 51,6% (n=33); between stimulus 11 and 20 in 37,5% (n=24) and between stimulus 21 and 28 in 10,9% (n=7). It was observed that 12,5% (n=8) of the children in this group were in neurobehavioral state 1; 20,3% (n=13) in 2; 28,1% (n=18) in 3 and 39,1% (n=25) in 4. Among the group of newborns that didn t present habituation of the blink reflex 36,1% (n=13) were male and 63,9% (n=23) female; none of them was in neurobehavioral state 1; 30,6% (n=11) was in 2; 8,3% (n=3) was in 3 and 61,1% (n=22) was in neurobehavioral state 4. We concluded that 64% of the newborns revealed habituation of the blink reflex; there was no significant association between gender and the occurrence of habituation; when in neurobehavioral state 3, neonates were six times more likely to present habituation of the blink reflex than in other neurobehavioral states and that the habituation phenomenon was present, predominantly, on the first 20 stimuli.